The Double Stitch Everting Technique in the End-to-Side Microvascular Anastomosis: Validation of the Technique Using a Randomized N-of-1 Trial - Dindelegan, George C.; Dammers, Ruben; Oradan, Alex V.; Vinasi, Ramona C.; Dindelegan, Maximilian; Volovici, Victor (Journal of Reconstructive Microsurgery, 2020)
Background The double stitch everting (DSE) technique, in which time is won by leaving the needle inside the vessel wall in-between stitching, is a modification of the end-to-side (ETS) anastomosis in the interest of reducing anastomosis time. This ensures proper wall eversion, intima-to-intima contact, and improved suture symmetry.Methods We designed an N-of-1 randomized trial with each microsurgeon as their own control. We included 10 microsurgeons of different levels of experience who were then asked to perform classic and DSE ETS anastomoses on the chicken leg and rat femoral models. Every anastomosis was cut and evaluated using blinded assessment. Two-way analysis of variance (ANOVA) and multivariable logistic regression were used to analyze the results and for confounder adjustment.Results A total of 210 anastomoses were performed, of which 177 on the chicken leg and 43 on the rat femoral artery and vein. From the 210 anastomoses, 111 were performed using the classic technique and 99 using the DSE technique. The mean anastomosis time was 28.8 ± 11.3 minutes in the classic group and 24.6 ± 12 minutes in the DSE group (p < 0.001, t-test). There was a significant reduction (p < 0.001, two-way ANOVA) in the number of mistakes when using the DSE technique (mean 5.5 ± 2.6) compared with those using the classic technique (mean 7.7 ± 3.4).Conclusion The DSE technique for ETS anastomoses improves anastomoses times in experienced and moderately experienced microsurgeons while also improving or maintaining suture symmetry and lowering the number of mistakes.
Keywords: anastomosis technique; validation study; cerebrovascular